Study of erectile dysfunction in patients of type 2 diabetes mellitus and its association with cardiovascular risk - Maury, Praveen Kumar; Agarwal, Saurabh; Giri, Richa; Ali, M. Fahad (International Journal of Advances in Medicine, 2022)
Background: Diabetes is a chronic metabolic disorder that is characterized by high level of blood glucose levels, which over a period of time can lead to micro-vascular or macro-vascular complications. Erectile dysfunction (ED) is common not much discussed and distressing complication of diabetes. ED in type 2 may be independent marker of coronary artery disease (CAD). Aim and objectives were to assess the ED in subject of type 2 diabetes mellitus (DM). Assessment of correlation of ED with CAD. Methods: The present cross-sectional study consisted total 180 diabetic patients. On basis of international index of erectile function (IIEF) questionnaire ED patients were assessed. Result: Out of 180 diabetic patients 36.11% had varying degree of ED. Out of 65 ED patients, maximum frequency of moderate ED (47.69%) was found then severe ED (32.30%), mild to moderate ED (12.30%) and mild ED (7.69%). Most of the patients were in the age group of 40-50 years 35 (53.84%), 50-60 years 22 (33.4%), <40 years (9.23%) and 60-70 years 2 (3.07%) showed ED. Fasting blood sugar and postprandial blood sugar showed significant (p<0.05) relation with ED. HbA1c show an insignificant correlation (p>0.05) with ED. In patient with ED was having more value of atherosclerotic cardiovascular disease (ASCVD) (9.11±4.84) than patient without ED (8.82±5.72). There was no significant (p>0.05) difference in term of ASCVD risk score in ED patient’s ED and without ED patients. Conclusions: Poor glycemic control was a strongest risk factor for ED.